2020
DOI: 10.1021/acs.nanolett.0c00752
|View full text |Cite
|
Sign up to set email alerts
|

A Nanoprimer To Improve the Systemic Delivery of siRNA and mRNA

Abstract: Despite tremendous interest in gene therapies, the systemic delivery of nucleic acids still faces substantial challenges. To successfully administer nucleic acids, one approach is to encapsulate them in lipid nanoparticles (LNPs). However, LNPs administered intravenously substantially accumulate in the liver where they are taken up by the reticuloendothelial system (RES). Here, we administer prior to the LNPs a liposome designed to transiently occupy liver cells, the Nanoprimer. This study demonstrates that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 29 publications
(38 reference statements)
0
56
0
Order By: Relevance
“…Cationic polymers, also termed as polycations, are extensively recognized as ideal and promising nonviral gene delivery vectors toward clinical gene therapy. [ 1–6 ] With the ability to bind and neutralize the anionic charges of nuclear acids (such as DNA), polycations are capable of condensing and packing DNA into complexes (or polyplexes) and thus facilitating the efficient intracellular internalization. [ 7,8 ] Unfortunately, most of the polycations usually suffered from the cationic charges induced cytotoxicity, that is, polycations with high positive charges always exhibit superb transfection efficiency whereas associated with undesired cytotoxicity.…”
Section: Methodsmentioning
confidence: 99%
“…Cationic polymers, also termed as polycations, are extensively recognized as ideal and promising nonviral gene delivery vectors toward clinical gene therapy. [ 1–6 ] With the ability to bind and neutralize the anionic charges of nuclear acids (such as DNA), polycations are capable of condensing and packing DNA into complexes (or polyplexes) and thus facilitating the efficient intracellular internalization. [ 7,8 ] Unfortunately, most of the polycations usually suffered from the cationic charges induced cytotoxicity, that is, polycations with high positive charges always exhibit superb transfection efficiency whereas associated with undesired cytotoxicity.…”
Section: Methodsmentioning
confidence: 99%
“…44 The formulation of this P-MOF-siRNA nanoparticles incorporated 500 nm siRN siRNA loading. 45,46 As an integrated nanosystem, hybrid nanoparticles are holding promising potential for further translation and application into the clinic.…”
Section: Hybrid Nanoparticlesmentioning
confidence: 99%
“…Nanoprimer pretreatment increased mRNA delivery, quantified by the expression of human erythropoietin, as well as siRNA delivery, quantified by factor VII gene silencing. [ 17 ] One key question that will need to be addressed when saturating Kupffer cells, or other hepatic cell types that act as clearance cells when nonhepatic delivery is wanted (e.g., hepatocytes, endothelial cells, dendritic cells), is considered as a pretreatment is tolerability, especially given the potential role Kupffer cell activation may play in dose‐limiting and systemic nanoparticle‐mediated toxicity. [ 18 ] Specifically, authors found that platelet‐activating factor, likely released by Kupffer cells, was a key driver of the immune response from nanoparticles carrying siRNA.…”
Section: Delivering Rna To Diseased Cells Is An Inefficient Multistep Processmentioning
confidence: 99%